Early Adverse Stress and Depressive and Bipolar Disorders: A Systematic Review and Meta-Analysis of Treatment Interventions - Martínez, Pablo; Gloger, Sergio; Diez de Medina, Dante; González, Arantza; Carrasco, María I.; Schilling, Sara; Vöhringer, Paul A. (Frontiers in Psychiatry, 2021)
Introduction: A significant proportion of adults with depressive or bipolar disorders exposed to early adverse stressors do not adequately respond to standard treatments. This review aimed at synthesizing the evidence on the effectiveness of treatment interventions for depressive or bipolar disorders in adult individuals (aged 18 years or more) exposed to adverse stress early in life. Methods: Systematic review and meta-analysis including experimental and quasi-experimental published studies indexed in CINAHL, EMBASE, PubMed, and Web of Science databases and/or in reference lists. Data management and critical appraisal (with the Study Quality Assessment Tools) was conducted independently by multiple researchers. A quality-effects model for meta-analysis was used for data synthesis and publication bias was assessed using the Doi plot and LFK index. The main outcome was short-term reductions in depressive symptoms. Results: Eight randomized controlled trials, three controlled before-and-after (pre-post) studies, and three uncontrolled before-and-after studies were included. Studies lacked bipolar disorder patients. Unclear randomization procedures and reporting of blinded outcome assessor, and limited use of intention-to-treat analysis, were relevant potential sources of bias. Meta-analyses indicated that psychological, pharmacological, and combined interventions were effective in reducing depressive symptoms in the short- (Cohen’s d = -0.55, 95% CI -0.75 to -0.36, I2 = 0%) and mid-term (Cohen’s d = -0.66, 95% CI -1.07 to -0.25, I2 = 65.0%). However, a high risk of publication bias was detected for these outcomes. A small number of studies, with mixed results, reported interventions with long-term improvements in depressive symptomatology, and short- and mid-term response to treatment and remission. Conclusion: Despite the well-documented long-lasting, negative, and costly impact of early adverse stressors on adult psychopathology, evidence on treatment alternatives remains scant. Trauma-focused treatment interventions – whether psychological interventions alone or in combination with pharmacotherapy – may have the potential to reduce the severity of depressive symptom in adults who were exposed to early adverse stress. Findings must be interpreted with considerable caution, as important study and outcome-level limitations were observed and gray literature was not considered in this systematic review and meta-analysis.